LAND USE CONVERSION: EVALUATION AND STRATEGIC ACTIONS - Ruth Roselin Nainggolan (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2017)
The conversion of agricultural land in Sumedang of the year 2005-2014 reached 317 hectares. The land generally converted into housing, office buildings and public facilities. This study aims to conduct a comprenhensive evaluation of the factors affecting changes in land use, analyze the impact of the changes and develop management strategies. This research was conducted with a qualitative approach located in Sumedang District, West Java Province. Sampling was done by multistage random sampling. The first step is selection of the sample subdistricts purposively with consideration of subdistricts that convert of land use at most, they are: Sumedang Selatan, Jatinangor and Jatigede. The second step sample selection by simple random to residents who do changes their agricultural land use. The data obtained from questionnaires, interviews,observations, study of documents and mass media. Working method is based on a modification of the stages of strategic planning for the company. Formulation of the strategy carried out through three phases: phase determination of the key internal and external factors, phase matching using the SWOT matrix, as well as the decision phase using QSPM matrix. The resulting strategy is implemented in a more technical work steps. The results showed the factors that affect farmers convert agricultural land is decreasing productivity of the land, accretion of family members, the right of inheritance of land, high land prices, construction of public facilities and government policy. The most dominant factor affecting is different in each district. The impact of changes in land use in general is the opening of new agricultural land by cutting down forests, decline in rice productivity and the emergence of new unemployment and alteration or loss of livelihood. From the SWOT analysis matrix, obtained three possible strategic options. First, a policy review of spatial and territories; second, to encourage farmers to maintain agricultural land by providing agricultural inputs and extension the use of organic materials to restore soil fertility and the third private land use change should be governed by strict licensing mechanism.